O CUIDADO A UMA PESSOA COM TAQUICARDIA ATRIAL PAROXÍSTICA: UM ESTUDO DE CASO CLÍNICO - GARCIA, CLEDIR T. F.; RIBAS, CRISTIANE; NAWROSKI, LUCIELE; DARONCO, VIVIAN F. (Salão do Conhecimento, 2013)
Resumo